1999
DOI: 10.1002/etc.5620180617
|View full text |Cite
|
Sign up to set email alerts
|

Lead exposure in passerines inhabiting lead‐contaminated floodplains in the Coeur D'Alene River Basin, Idaho, USA

Abstract: Abstract-Blood collected from song sparrows (Melospiza melodia) and American robins (Turdus migratorius) captured with mist nets in a lead-contaminated (assessment) area and nearby uncontaminated (reference) areas within the Coeur d'Alene Basin in northern Idaho was analyzed for ␦-aminolevulinic acid dehydratase activity (ALAD) and hematocrit levels, and livers were analyzed for lead. Mean ALAD inhibition in the assessment area was 51% in song sparrows and 75% in American robins. The proportion of the sampled … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 20 publications
1
7
0
Order By: Relevance
“…A total of 9% of song sparrows and 70% of robins from the severely contaminated sites had blood Pb concentrations above the clinical poisoning threshold. Inhibition of ALAD activity in red blood cells of these species demonstrates the severity of the exposure in the basin and corroborates an earlier finding of 51% inhibition in song sparrows and 75% inhibition in robins in 1995 (Johnson et al 1999). Elevated hepatic Pb concentrations (Tables 2 and 4) further confirm that Pb in the basin is hazardous to ground-feeding songbirds.…”
Section: Effects On Songbirdssupporting
confidence: 87%
See 1 more Smart Citation
“…A total of 9% of song sparrows and 70% of robins from the severely contaminated sites had blood Pb concentrations above the clinical poisoning threshold. Inhibition of ALAD activity in red blood cells of these species demonstrates the severity of the exposure in the basin and corroborates an earlier finding of 51% inhibition in song sparrows and 75% inhibition in robins in 1995 (Johnson et al 1999). Elevated hepatic Pb concentrations (Tables 2 and 4) further confirm that Pb in the basin is hazardous to ground-feeding songbirds.…”
Section: Effects On Songbirdssupporting
confidence: 87%
“…Blus et al (1995) found that nestlings of 7 American robins collected in the basin had blood Pb concentrations ranging from 0.27 to 0.87 mg/kg wet weight. Audet (1997) found elevated blood and hepatic Pb concentrations and inhibited blood ALAD activity in a small sample of song sparrows (Melospiza melodia) and American robins, and Johnson et al (1999) documented elevated hepatic Pb concentrations and inhibited ALAD activity in song sparrows. Because of the suggested risk to songbirds (USEPA 2001(USEPA , 2002 and because of the importance of the basin as wildlife habitat, we sampled ground-feeding songbirds throughout the basin to determine if they were exposed to toxic concentrations of Pb and to find the pathway of exposure.…”
Section: Introductionmentioning
confidence: 99%
“…The American robin, song sparrow, and Swainson's thrush were selected as representative ground-feeding songbirds because they are relatively abundant in the basin, previous data for these species had been collected (Blus et al 1995;Audet et al 1999;Johnson et al 1999), and the basin-wide ERA concluded that these 3 species were at relatively high risk. These songbirds spend much of the spring and early summer feeding on invertebrates in and on the ground.…”
Section: Ecological Conceptual Site Modelmentioning
confidence: 99%
“…As a result, migratory birds have been exposed to and adversely affected by Pb in multiple habitats in the basin (Blus et al 1995;Audet et al 1999;Johnson et al 1999;Beyer et al 2000). Tundra swans (Cygnus columbianus), Canada geese (Branta canadensis), mallards (Anas platyrhynchos), and other waterfowl have often been found dead in the basin from the toxic effects of ingesting Pb-contaminated sediment Beyer et al 2000;Sileo et al 2001).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation